The hyperactive child and the body: a clinical study on the origin of hyperactivity in children A criança hiperativa e seu corpo: estudo clínico sobre a gênese da hiperatividade em crianças - Ceme Ferreira Jordy; Regina Célia Gorodscy (Arquivos de Neuro-Psiquiatria)
A group of 22 hyperactive children from 7 to 12 years of age was selected among 38 out-patients registered at Hospital do Servidor Público de São Paulo (Civil Servant Hospital of the State of São Paulo). Their psychiatric evaluation was negative, the neurological examination showed "psychomotor syndrome", and psychological evaluation revealed disorders related with Ego maturation in all cases. Although all children were referred to psychotherapy, only thirteen underwent individual sessions once a week for an uninterrupted period of up to one year. Neither diets nor medicines were prescribed. After six months and one year of treatment, the children were reevaluated. They showed improved school performance, reduced hyperactivity, and better internal psychic organization. These results are considered as undeniable evidence of the psychodynamic origin of hyperactivity syndrome in children, when no definite neurologic or psychiatric diseases are demonstrated. Vinte e duas crianças hiperativas, de 7 a 12 anos de idade foram selecionadas dentre 38 matriculadas no Ambulatório de Psiquiatria do Hospital do Servidor Público do Estado de São Paulo. A avaliação psiquiátrica foi negativa, o exame neurológico revelou síndrome psicomotora, a avaliação psicológica evidenciou transtornos relacionados com maturação do Ego em todos os casos. Encaminhadas à psicoterapia, apenas 13 crianças puderam atender a sessões individuais e semanais, por um período ininterrupto de seis meses a um ano. Nem dietas nem medicamentos foram prescritos. Reavaliação feita após seis meses e um ano, revelou redução da hiperatividade, aumento do rendimento escolar e melhor organização psíquica interna. Estes resultados são considerados forte evidência da origem psicodinâmica da síndrome hiperativa em crianças neurologicamente normais.